Kepemimpinan Kapuangan Balusu dan Relevansinya Terhadap Peran Pandu Budaya Gereja Toraja - Palamba', Simon (KINAA: Jurnal Kepemimpinan Kristen dan Pemberdayaan Jemaat, 2022)
Abstract: The Balusu are indigenous peoples who are in the kaparengesan leadership area who also apply the kapuangan leadership. This leadership model finds a unique form. In addition, this community context is the site of the presence of the Toraja Church. So, this article aims to review the leadership model of the kapuangan Balusu and build the Toraja Church response with the perspective of the role of cultural guides that has been rolled out since the holding of the Toraja Ma’kombongan which emphasizes that there has been a shift in values ​​and meanings in various Toraja cultural practices. This meeting proposed the reinterpretation and actualization of Toraja culture. Therefore, the Toraja Church is responsible for taking on a guiding role in each of its local contexts. We want to contribute to the discourse on reinterpreting Toraja culture, specifically the kapuangan leadership model. The description of this article involves qualitative research methods, namely literature studies and interviews with traditional leaders in Balusu. In the end, this article attempts to review the kapuangan leadership model in Balusu in relation to the role of cultural guides by the Toraja Church to carry out Christian transformation. Abstrak: Balusu merupakan masyarakat adat yang berada dalam wilayah kepemimpinan kaparengesan yang juga menerapkan kepemimpinan kapuangan. Model kepemimpinan ini menemukan bentuk unik. Selain itu, konteks masyarakat ini merupakan situs kehadiran Gereja Toraja. Maka, artikel ini bertujuan untuk mengulas model kepemimpinan kapuangan Balusu dan membangun Gereja Toraja dengan perspektif peran pandu budaya yang telah digulirkan sejak diselenggarakannya Toraja Ma’kombongan yang menandaskan bahwa telah terjadi pergesaran nilai dan makna dalam berbagai pelaksanaan budaya Toraja. Pertemuan ini mengusulkan reinterpretasi dan reaktualisasi budaya Toraja. Karena itu, Gereja Toraja bertanggung jawab mengambil peran pandu di masing-masing konteks lokalnya. Kami hendak memberikan sumbangsi diskursus reinterpretasi budaya Toraja, secara khusus model kepemimpinan kapuangan di Balusu. Uraian artikel ini melibatkan metode penelitian kualitatif, yakni studi pustaka dan wawancara dengan tokoh-tokoh adat di Balusu. Pada akhirnya, artikel ini berupaya untuk mengulas model kepemimpinan kapuangan di Balusu dalam kaitannya dengan peran pandu budaya oleh Gereja Toraja untuk melakukan transformasi kristiani.